Associations between adductor strength; flexibility and self-reported symptoms in elite professional footballers: a case series. Issue 2 (3rd April 2019) - Light, Neil; Gimpel, Mo; Sparks, Steve; Bowen, Laura; Bruce-Low, Stewart; Hughes-Jones, Zoe
ABSTRACT: Objectives: Measures of adductor strength, flexibility and self-reported symptoms offer insights into footballer hip/groin health. Understanding their relationship may further determine their suitability for use.Design: Clinical case series Method: Eighteen professional footballers completed two adductor squeeze tests (short and long lever), the HAGOS (sport) and Bent Knee Fall Out (BKFO); 2 days post-match, during a period of 4 months.Results: Adductor strength reduced beyond the minimal detectable change (MDC) on 16 occasions for the long-lever squeeze (MDC = 7%) and 7 occasions for short-lever squeeze (MDC = 15%). On 17 occasions, participant BKFO scores reduced beyond the MDC (21%). A relationship between both squeeze tests and HAGOS (sport) was observed explaining 12% variance for short-lever ( R 2 = 0.121, p = 0.006) and 7% for long-lever ( R 2 = 0.065, p = 0.046) tests. The BKFO showed no statistically significant ( P = > 0.05) correlation to either squeeze test ( r p = 0.153/0.193) or HAGOS (sport) ( r p = 0.182).Conclusion: This study adds to literature surrounding monitoring of hip/groin measures in footballers. The long-lever adductor squeeze detected meaningful changes more frequently than the short-lever. Both tests shared weak, albeit statistically significant relationships with HAGOS (sport), whilst the BKFO did not. A larger prospective study is warranted to increase confidence in selecting these measures in this setting.